Data Analysis and Visualization by extracting insights for Efficient Project Planning - Ansari, Syed Tameem; Nasreen, Azra (International Journal of Computer Sciences and Engineering, 2020)
Data analysis and Visualization is a new and trending field in computer science. Visualizations represent a means to communicate data and analysis results. It uses graphic effects to reveal patterns, trends and relationships out of data. It involves in representation of data in pictorial or graphical form which makes the information easy to understand. Visualization and data analysis can be performed on many tools such as Tableau, Apache spark, Excel spread sheets. Visualization and data analysis using Power BI is affordable, quite simple and easy to develop and maintain as it supports real time data processing. Multiple data sources can be used to imported data for analysis into Power BI for developing custom visualizations that helps in-detail understanding of resources and budget used in development and management of a project. M-query and DAX are the functional languages used to extract insights, merge or append queries, create new measures and new custom columns for developing attractive and self-explanatory dashboards about resources in developing and maintaining projects. Visualizations and data analysis help in better prediction and forecasting for the future projects in the organization, these visualizations and dashboards can be shared on cloud based BI environment at managerial level and respective lower levels with row level security.